Analysis of the temporal and spatial pattern of air pollution and the heterogeneity of its influencing factors in central Inner Mongolia from 2016 to 2018 - Wang, Jie; Liu, Dongwei; Xu, Xijie; Ma, Jiali; Han, Lijing (Frontiers in Environmental Science, 2022)
The central region of Inner Mongolia is the northern ecological safety barrier of Beijing and even the whole country. It is one of the main sources of dust in North China, and air pollution control is the top priority in this region. In this study, the central region of Inner Mongolia was selected as the study area, multiple auxiliary variables were used to estimate the spatial distribution of PM2.5 concentration from 2016 to 2018 by geographically weighted regression, and the socioeconomic determinants of PM2.5 concentration were analyzed by geographic detectors. The results show that: (1) the established model can better estimate the spatial distribution of PM2.5 concentration in the study area, and the monthly average correlation coefficient R of the verification parameters is stable, ranging from 0.58 to 0.66. (2) PM2.5 concentration in central Inner Mongolia showed significant temporal and spatial variation. The average annual PM2.5 concentration along the Yellow River basin is the highest in the study area. PM2.5 concentration first increased and then decreased from 2016 to 2018. (3) Urban built-up area, permanent population and per capita GDP are the key factors affecting the spatial and temporal distribution of PM2.5 concentration in the study area. The results of this study provide theoretical basis and technical support for air pollution monitoring, management and prevention in central Inner Mongolia.